HUBUNGAN ANTARA PENGETAHUAN TENTANG KANKER PAYUDARA DENGAN PELAKSANAAN BREAST SELF EXAMINATION (BSE)/ PEMERIKSAAN PAYUDARA SENDIRI (SADARI) - Fitria Jannatul Laili; Ai Nur Jannah; Siti Mudawamah (Jurnal Kesehatan dr. Soebandi, 2016)
Introduction: breast cancer is the second most frequent cancer among worldwide and the leading form of cancer among women. Its incidence having increased significantly over recent decades. Early detection and effective treatment are the most important factors that can reduce the morbidity and mortality associated with breast cancer. One of the methods of early detection is bse. Midwifery students have responsibility not only for improvement knowledge and care of women about prevention breast cancer, in particular with bse, but also improvement of own health. Bse as a health behaviour is influenced of many factors, for example is knowledge. The purpose: to know correlation between knowledge of breast cancer and bse of midwifery student on medicine faculty airlangga university. Methodology: this study was analitical method by cross-sectional in its design to see correlation between knowledge of breast cancer as independent variable and bse as a dependent variable. Populations in this study were midwifery students which are consisted of 100 people. Sample was taken by probability sampling with amount 88 respondents. The instrument for collecting data was questioner. Data analysis was used coefficient correlation spearman rank. Results: those were 25% respondents who had lack knowledge about breast cancer remainder had enough (43,18%) and knowledgeable (31,82%). Beside that, most of respondents had performed bse (48%) but only 7,95% who had performed bse regularly. This study showed that be found moderate correlation and significant between knowledge of breast cancer and bse of midwifery students (p-value=0.003; α=0.05) with coefficient correlation spearman rank was 0.26.Conclusion: knowledge about breast cancer has contribution approximately 28,57% to perform bse. There is hoped that midwifery students can perform bse regularly and always improve about knowledge of breast cancer so they can educate other women about this important preventive procedure. Besides that it is also expected to be conducted a furthermore research about factors that influence to base.